Occurrence of Antibiotic Resistance in the Mediterranean Sea - Delia Gambino; Dario Savoca; Arianna Sucato; Valeria Gargano; Antonino Gentile; Licia Pantano; Domenico Vicari; Rosa Alduina (MDPI AG, 2022)
Seawater could be considered a reservoir of antibiotic-resistant bacteria and antibiotic resistance genes. In this communication, we evaluated the presence of bacterial strains in seawater collected from different coasts of Sicily by combining microbiological and molecular methods. Specifically, we isolated viable bacteria that were tested for their antibiotic resistance profile and detected both antibiotic and heavy metal resistance genes. Both antibiotic-resistant Gram-negative bacteria, Vibrio and Aeromonas, and specific antibiotic resistance genes were found in the seawater samples. Alarming levels of resistance were determined towards cefazolin, streptomycin, amoxicillin/clavulanic acid, ceftriaxone, and sulfamethoxazole/trimethoprim, and mainly genes conferring resistance to β-lactamic and sulfonamide antibiotics were detected. This survey, on the one hand, presents a picture of the actual situation, showing the pollution status of the Tyrrhenian coast of Sicily, and, on the other hand, can be considered as a baseline to be used as a reference time for future analysis.